2016
DOI: 10.1016/j.mechmat.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation and modification of surface characteristics in nano- and micro-levels and enhancement of electric field of FCC materials using cavitation phenomenon

Abstract: The aim of this paper is to demonstrate and establish a possible application of the cavitation phenomenon as an efficient method to modify surface properties. Three FCC (Face Centered Cubic) materials were subjected to high speed submerged cavitating jets under certain working conditions, for time periods between 15 and 1,800 s. The force generated by cavitation is employed to modify the surface roughness in nano and micro scales. The target surface was investigated with digital optical microscopy, atomic forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In order to improve the performance of high speed waterjet while at the same time keep the supplying pressure relatively low, cavitating and pulsed waterjets have been put forward. In terms of a cavitating waterjet, the collapse of cavitation bubbles in the free shear layer produces not only mechanical impact but also high temperature spots, which can cause serious damage to the nearby solid surface [4][5][6] . For a pulsed waterjet, the highly enhanced destructive effect comes from the high-intensity and short-duration water hammers with transient pressure pulses caused by a series of discrete water slugs [7] .…”
Section: Introduction mentioning
confidence: 99%
“…In order to improve the performance of high speed waterjet while at the same time keep the supplying pressure relatively low, cavitating and pulsed waterjets have been put forward. In terms of a cavitating waterjet, the collapse of cavitation bubbles in the free shear layer produces not only mechanical impact but also high temperature spots, which can cause serious damage to the nearby solid surface [4][5][6] . For a pulsed waterjet, the highly enhanced destructive effect comes from the high-intensity and short-duration water hammers with transient pressure pulses caused by a series of discrete water slugs [7] .…”
Section: Introduction mentioning
confidence: 99%
“…We demonstrated that cavitation could be utilized as a tool to purposefully modify the surface characteristics of these materials (in other worlds increase their surface roughness in a controllable fashion) in the micro-and nano-levels [52,53]. The relation between the behavior of the cavitation erosion process and the geometrical parameters of the generator (e.g.…”
Section: Micro-and Nano-scale Materials Characterizationmentioning
confidence: 99%
“…On the other hand, the destructive power of cavitation can be deliberately used to modify and enhance the surface or mechanical properties of target materials, e. g. for cleaning, cutting or peening with relatively low energy consumption. Cavitating water jets have received much attention also in the environmental industry for the possibility to use them for the decomposition of toxic substances and the water treatment [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Until now many experimental --------------studies on cavitating water jets have been made concerning jet driven pressure, shape and size of a nozzle, cavitation number, etc. [1,2,[5][6][7]. However, the structure of the cavitating jet and the behavior of the unsteady cavitation bubbles are still in question, mostly due to the difficulty to observe the interior of cavitating flows [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation